2016
DOI: 10.22159/ijpps.2016.v8i9.12434
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging and Disinfectant Effect of Essential Oil From Moroccan Mentha Pulegium

Abstract: Objective: As part of the valorization of medicinal and aromatic plants in Morocco, this study aims to investigate the chemical composition, the antimicrobial and the antioxidant activities of Mentha pulegium essential oil.Methods: Essential oil of M. pulegium from Oued Laou region (Morocco) was screened for its antimicrobial activity against seven bacteria and two fungi using broth microdilution method. The radical scavenging effect was used to assess in vitro antioxidant capacity of this oil. Results:The tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Similarly, Nikolić et al (2014) reported that Mentha pulegium EO displays higher antimicrobial activity than Lavandula angustifolia EO. This antimicrobial activity is mainly attributed to the presence of major compounds in the composition of the EOs, namely phenols, terpenes, and oxygenated monoterpenes (Chraibi, Fikri Benbrahim, Ou‐yahyia, Balouiri, & Farah, 2016). In our case, Mentha pulegium EO was rich in pulegone and carvacrol (Aitboulahsen, Zantar, Amin, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Nikolić et al (2014) reported that Mentha pulegium EO displays higher antimicrobial activity than Lavandula angustifolia EO. This antimicrobial activity is mainly attributed to the presence of major compounds in the composition of the EOs, namely phenols, terpenes, and oxygenated monoterpenes (Chraibi, Fikri Benbrahim, Ou‐yahyia, Balouiri, & Farah, 2016). In our case, Mentha pulegium EO was rich in pulegone and carvacrol (Aitboulahsen, Zantar, Amin, et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Also, LEO has a significant antimicrobial activity as shown by Soković, Glamočlija, Marin, Brkić, and van Griensven (). The antimicrobial activity of these two EOs was mainly due to their chemical composition rich in pulegone for M. pulegium (Chraibi, Fikri Benbrahim, Ou‐yahyia, Balouiri, & Farah, ) and linalool and linalyle acetate for L. angustifolia (Giovannini et al, ). These bioactive compounds penetrate the lipid structure of the bacterial cell membrane, leading to its destruction.…”
Section: Resultsmentioning
confidence: 99%
“…Although, the essential oils consist of various properties, there are also certain limitations which are due to their volatile and hydrophobic nature. So, these problems may be overcome by recent trends, such as formulating essential oils into nanoemulsion, due to their transparency, solubility in water and also less amount of essential oil is required (Qian et al, 2012) [6][7][8][9][10][11]. An attempt was made to formulate the Mentha piperita essential oil as nanoemulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Because, the genus M. piperita is commonly known as peppermint, it is a cultivated natural hybrid of two species, Mentha aquatic L and Mentha spicata L. (Saller, 2004) and it is cultivated worldwide (Foster, 1996). The M. piperita essential oil is known to have antimicrobial (Chraibi et al, 2016), antioxidant (Singh et al, 2015) and insecticidal (Kumar et al, 2011) activity. The present study aims to evaluate the insecticidal activity of M. piperita essential oil nanoemulsion against the serious agricultural pest, H. vigintioctopunctata (adult beetles).…”
Section: Introductionmentioning
confidence: 99%